A Criminological Study Of Premeditated Murder Committed By A Child Against His Biological Father - Ramadhany Nasution (Fox Justi : Jurnal Ilmu Hukum, 2025)
Murder is an act of intentionally taking the life of another person where life is a gift from God Almighty and no one can eliminate it. This type of research is normative with a statutory approach. The data used is secondary data consisting of primary, secondary and tertiary legal materials. Criminological studies of premeditated murder by children against their biological fathers can be reviewed from the theories of biology, economics, sociology, psychology and economics. The causative factors are due to poor environmental factors, economic crush, emotional instability and past traumas. In addition, it can also be caused by feeling betrayed, harmed, or humiliated, jealousy and anger. For this reason, it is necessary to educate and create harmonious relationships between family members so that premeditated murder by a child against his father can be avoided. So that everyone avoids the crime of premeditated murder because the sanctions are very severe and violate other human rights, especially against his own father who has been very instrumental in the life of the child and so that law enforcers impose penalties on perpetrators of premeditated murder in accordance with applicable regulations to cause a deterrent effect.